Does Aid translate into Bilateral Trade? Findings for Recipient Countries - Felicitas Nowak-Lehmann D.; Inmaculada Martínez-Zarzoso; Adriana Cardozo; Dierk Herzer; Stephan Klasen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper uses the gravity model of trade to investigate the link between foreign aid and exports in recipient countries. Most of the theoretical work emphasizes the negative impact of aid on recipient countries' exports primarily due to exchange rate appreciation, disregarding possible positive effects of aid in overcoming supply bottlenecks and promoting bilateral trade relations. Our empirical findings -all based on endogeneity-proof techniques (such as Dynamic OLS or more refined techniques) - depend very strongly on whether bilateral trade relations and autocorrelation of the disturbances are controlled for. When not controlling for these phenomena, the impact of aid is quite substantial (especially in Asia, Latin America & Caribbean) but when sound estimation techniques are applied the net impact of aid on recipient countries' exports becomes insignificant in the full 130-country sample and the subsamples: Sub-Saharan Africa & MENA, Asia and Latin America & the Caribbean. However, this rather disappointing finding is in line with the small macroeconomic impact of aid found in earlier studies.
Keywords: F10; F35; 330; International trade; foreign aid; recipient exports; bilateral trade relations